Validity and Reliability of the Patient Health Questionnaire (PHQ-9) Instrument among School Students - Yazid , Haziq Azree; Mohd Sa’ad, Fauziah (Jurnal Pendidikan Bitara UPSI, 2024)
This study aims to assess the validity and reliability coefficients of the Malay version of the Patient Health Questionnaire-9 (PHQ-9) instrument among school students. The instrument was translated from the PHQ-9, developed by Kroenke et al. (2001). PHQ-9 is used to measure depression symptoms according to the criteria in the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV-TR). The validity and reliability testing was conducted on the PHQ-9 instrument because no prior study has examined how suitable the Malay version of PHQ-9 is for use among school students in Malaysia. Content validity needed to be re-evaluated as the sentence structure in each item required refinement to ensure that every item was fully understood by respondents. The instrument was first evaluated by seven expert panels before being distributed to the study respondents. A pilot study involving 327 students aged 16 and 17 from two states in Malaysia, Negeri Sembilan and Selangor, was conducted to obtain the reliability value of the instrument using the Statistical Package for Social Sciences (SPSS) version 26.0. The results showed that PHQ-9 had a high content validity index (CVI) of 0.87, based on expert panel ratings. The findings also indicated that PHQ-9 had a high reliability value, with a Cronbach’s Alpha of α=0.84. In conclusion, the Malay version of the PHQ-9 instrument can be used to identify the level of depression among school students, as it has proven to have high validity and reliability. Students diagnosed with high levels of depression should be given early treatment to prevent more serious mental health issues.